2017
DOI: 10.1002/cbin.10794
|View full text |Cite
|
Sign up to set email alerts
|

C‐X‐C motif chemokine receptor 4 promotes tumor angiogenesis in gastric cancer via activation of JAK2/STAT3

Abstract: C-X-C motif chemokine receptor 4 (CXCR4) overexpression promotes gastric cancer growth and metastasis. In this study, we determined its role in regulating tumor angiogenesis. We overexpressed CXCR4 in gastric cancer cells and examined the effects of conditioned medium on endothelial cell proliferation, migration, and tube formation. The effects of CXCR4 overexpression on vascular endothelial growth factor (VEGF) expression and signal transducer and activator of transcription 3 (STAT3) activation were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In addition, gefitinib obviously inhibited the phosphorylation of ERK1/2 and STAT3 in H3255 xenograft model. Previous results showed that STAT3 could be activated by EGFR to participate in oncogenesis and was simultaneously involved in angiogenesis, especially the expression of VEGF‐A . In our study, gefitinib also inhibited the expression VEGF‐A in H3255 xenograft model.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, gefitinib obviously inhibited the phosphorylation of ERK1/2 and STAT3 in H3255 xenograft model. Previous results showed that STAT3 could be activated by EGFR to participate in oncogenesis and was simultaneously involved in angiogenesis, especially the expression of VEGF‐A . In our study, gefitinib also inhibited the expression VEGF‐A in H3255 xenograft model.…”
Section: Discussionsupporting
confidence: 72%
“…To further elucidate the mechanism underlying these phenomenons, SystemsDock (http:// systemsdock.unit.oist.jp/), a web server for network pharmacology-based prediction and analysis was applied [20]. Emerging evidence has suggested that the JAK2/STAT3 pathway participates in the regulation of angiogenesis [26], and blockade of the JAK2/STAT3 pathway could inhibit tumor growth. To explore whether JAK2/STAT3 signaling pathway is the therapeutic targets of ORI, we applied SystemsDock.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [34] confirmed the role of JAK2/STAT3 pathway in mediating VEGF expression upon Ginkgolide K treatment after ischemic stroke. Zhang et al [35] demonstrated that C-X-C motif chemokine receptor 4 induced JAK2/STAT3 activation and enhanced STAT3 binding to VEGF promoter and then potentiated VEGF production in gastric cancer cells. Meanwhile, recent studies also revealed that autophagy directly regulats JAK2/STAT3 signaling pathway in lung cancer cells [19].…”
Section: Discussionmentioning
confidence: 99%